Confronting the Colonies : British Intelligence and Counterinsurgency. - Cormac, Rory (Oxford University Press, 2014)
An original exploration of how the intelligence community became aware of the growing insurgent threat in the twilight of Empire, the challenges this posed, and its impact upon how Whitehall saw the world.